Kesesuaian Galur Padi (Oryza sativa) pada Lahan Sawah Tadah Hujan - Susanto, Untung; Arifin, Samsul; Rohaeni, Wage R.; Wening, Rina H. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
Rice productivity in rainfed area is mostly determined by the environmental condition, cultivation technique, specific stress occurrence, and the variety planted. There are around 4 million ha of rainfed lowlands in Indonesia, contributing the second biggest supply for national rice production after the irrigated area. Planting the most suitable rainfed lowland rice variety is expected to increase rice yield in the area. This research was aimed to test 34 rainfed lowland rice lines along with five check varieties in two targeted areas, i.e. Purwakarta during Dry Season 2015 (transplanting technique of 21 days old seedlings) and Pati during Wet Season 2015/2016 (using direct seeded or gogo rancah planting method). The treatments were arranged in a randomized complete block design with three replications, at 3 x 5 m2 plot, and 25 cm x 25 cm plant spacing. Results showed the existence of genetic x environment interactions of all observed traits, except for tiller number. Grain yield, tiller number, and number of filled grains/panicle in Purwakarta was each higher than that in Pati. Seven lines were identified as having high yield in Purwakarta and were medium in Pati, and five lines were high yield in Pati and were medium in Purwakarta. Line IR83383-B-B-129-4 (10.35 t/ha) yielded higher compared to the best check Inpari 13 (8.27 t/ha) in Purwakarta. Most of lines in Pati had comparable yield with the best check Inpari 23 (7.18 t/ha). Grain yield was positively correlated with number and percentage of filled grains/panicle and negatively correlated with number of unfilled grains/panicle. Keywords: R